STUDI KOMPARASI PENGGUNAAN SIMPLISIA DAUN MANGGA DAN DAUN SIRIH UNTUK MEMPERPANJANG MASA SIMPAN IKAN PADA PENGEWETAN MENGGUNAKAN ES - Agus Darwanto; Gradien Ridholumintu; Raihan Anwar Musyadad (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2022)
Traditional fishermen in fishing operations use equipment that is still simple with preservatives in the form of ice cubes which can only prevent damage to fish for 2-3 days. The purpose of the study was to find out how to use mango leaves as an additional ingredient in the process of preserving fish by cooling using ice and the effectiveness of using mango leaves compared to betel leaves as a positive control in maintaining the freshness of fish quality. Collecting data using sensory test, ALT Aerob analysis test, TVB-N analysis test and E. coli analysis test. The use of mango leaves for simple fish preservation can be done by traditional fishermen by making simplicia through the process of cutting, drying and grinding. Based on the sensory test, it was found that the use of mango leaf simplicia was able to maintain the freshness and durability of fish products caught by fishermen, much better than the use of ordinary ice because the value of F > F crit and < 0.05. Based on the analysis of the BNT/LSD test, it is known that there is a significant difference between the use of mango leaves which is much better than the use of betel leaves for eye brightness parameters, but there is no significant difference between the use of mango leaves and betel leaves for scale color parameters and fish aroma. Aerobic ALT analysis found levels of 5,113 colonies/gram which was still relatively good because it was below 500,000 colonies/gram. TVB-N analysis obtained levels of 27.77 mg/100 grams which are still categorized as suitable for consumption because they are below 30 mg/100 grams. Meanwhile, E. coli levels were below 3 APM/gram. So that the addition of mango leaf simplicia has a real effect in maintaining the freshness and quality of fish in preservation using ice.